A new species of coral snake (Serpentes, Elapidae) from the Sierra de Tamaulipas, Mexico - Lavin-Murcio, Pablo A.; Dixon, James R. (Phyllomedusa: Journal of Herpetology, 2004)
We describe a new species of Micrurus from the Mexican state of Tamauliupas. All of our specimens were encountered in pine-oak forest above an elevation of 750 meters. The new species is related to Micrurus tener, but differs in the absence of a yellow parietal ring and the presence of a tricolored tail.